2011
DOI: 10.1097/bot.0b013e3181eaaf52
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Function and Quality of Life in Elderly Patients After a Subtrochanteric Femoral Fracture Treated With a Cephalomedullary Nail

Abstract: A subtrochanteric fracture treated with a single lag screw cephalomedullary nail had a substantial negative impact on the patient's musculoskeletal function according to the Short Musculoskeletal Function Assessment as well as on the patient's health-related quality of life. However, the need for revision surgery was comparatively low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 32 publications
(28 reference statements)
2
23
2
1
Order By: Relevance
“…Our study showed that mean preoperative EQ-5D index scores of both groups were 0.61 and 0.62 respectively. These results were consistent with prior studies [34,35]. In sequential scheduled visits, at the 3 rd , 12 th and 24 th month postoperatively, EQ-5D index scores increased significantly in both groups, indicating an increase in life quality for the patients; however, the scores never reached the preoperative levels.…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed that mean preoperative EQ-5D index scores of both groups were 0.61 and 0.62 respectively. These results were consistent with prior studies [34,35]. In sequential scheduled visits, at the 3 rd , 12 th and 24 th month postoperatively, EQ-5D index scores increased significantly in both groups, indicating an increase in life quality for the patients; however, the scores never reached the preoperative levels.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, this technique has been shown to be associated with the development of fat embolism and adult respiratory distress syndrome (ARDS), both of which can be fatal12). Therefore, special care should be taken to avoid fatal complications following surgical treatment for subtrochanteric fracture of the femur, especially in patients with multiple trauma including lung injury345).…”
Section: Introductionmentioning
confidence: 99%
“…Miedel et al [11] too, investigated and documented a statistically significant deterioration in quality of life between prefracture and the 12 months follow-up examination of 109 unstable pertrochanteric fractures treated with a GN. Comparable to the findings of 2005 [11] Miedel et al published a study with 53 patients treated with a LGN for subtrochanteric fractures showing worse outcomes in musculoskeletal function and quality of life after a 12 months follow-up [15]. …”
Section: Discussionmentioning
confidence: 90%
“…Due to this focus, patient based outcomes such as health related quality of life have been given less attention [10-15]. …”
Section: Introductionmentioning
confidence: 99%